Faktor-faktor yang mempengaruhi tingkat kecemasan pasien fraktur tulang panjang pra operasi yang dirawat di rsud arifin achmad Pekanbaru - Winda, Rizky Ika; Nauli, Fathra Annis; Hasneli, Yesi - (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Keperawatan, 2014)
The purpose of this research was to determine the factors that influence anxiety levels of long bone fracture pre operation patients who hospitalized in Arifin Achmad Hospital Pekanbaru. This research used descriptive correlation design with cross sectional approach. This research was conducted in Arifin Achmad Hospital Pekanbaru with 30 people who had long bone fracture and selected based on inclusion criteria. The measuring instrument was questionnaire that had been tested for validity and reliability. The analysis used are univariate and bivariate used Chi Square test. The result of this research showed that there are significant relationship between socio economic status (p value = 0,049) with patient’s anxiety, and there are no significant relationship between nursing services (p value = 0,440), level of knowledge (p value = 0,024), family support (p value = 0,127) with patient’s anxiety. The result of this study recommend for hospital to increase in psychosocial nursing care and help in directing adaptive coping mechanisms to patient’s who hospitalized so that reduce anxiety. Key words: Anxiety, family sopport, knowledge, long bone fracture, nursing services, socio economic status